The Physician as a Health Care Proxy - Rai, Arti (The Hastings Center report, 1999)
Many states prohibit patients from appointing their physicians as health care proxies, fearing paternalism and conflict of interest. But the potential for conflict is not unique to physicians, and patients may have compelling reasons to prefer that their doctor make decisions on their behalf. Managing potential conflicts serves patients better than denying them the right to choose who will make health care decisions for them when they are no longer competent.